Scoping Review: Patient preference for Traditional Chinese Medicine (TCM) in China - Wei, Min (Animo Repository, 2022)
Traditional Chinese Medicine (TCM) is an important part of the medical and health system in China. However, an in-depth understanding of patients’ preferences and influencing factors for TCM services within China has yet to be explored in depth. Therefore, this scoping review aims to map out the relevant academic literature on the preferences and influencing factors of patients for TCM in China, identify relevant research gaps, and propose directions for future research in this area of knowledge. This scoping review adopted the protocol of the PRISMA-ScR. Searches in the PubMed, Science Direct, EMBASE, and China National Knowledge Infrastructure (CNKI) databases gleaned 16,552 results that were published from 2010 to 2019 that met pre-set criteria. Of these, 10,732 duplicates were removed, resulting in 5,820 articles being screened by title and abstract. Screening by title and abstract excluded 5,529 articles resulting in 291 articles left for full- text review. These 291 articles underwent full-text review, resulting in a total of 259 articles being excluded and 32 articles being deemed relevant to this scoping review. All data were charted and analyzed using charting tables to allow data to be mapped out, analyzed for gaps, and for directions for future research to be suggested. The gaps identified include complex factors influence TCM preference among patients in China, present research on TCM preference is neither extensive nor in-depth, low levels of research from the standpoint of personal characteristics as well as treatment process factors and external factors, and insufficient research on the relationship between different factors influencing preference and the complex mechanism of preference formation. Future directions of research include extensive and in-depth research on the relationship between different factors influencing TCM preference, the study of the complex mechanism of TCM preference formation, the influence of personal characteristics on TCM preference, and the complexity of factors that influence TCM preference among patients in China.